Comparison between kinesiotherapy and back school in the treatment of low back pain in older adults - Sonia Maria Marques Gomes Bertolini; Maria Lúcia Ziroldo (Universidade Federal do Ceará, 2015)
Objective: to compare the efficacy of physiotherapy treatment involving kinesiotherapy and back school in older adults' lowback pain. Methods: study of the case-series type. The pain visual analog scale and the WHOQOL-bref were used for assessingquality of life, and the Timed Up and Go Test was used for testing agility. A total of 21 older adults, who had had low back painfor over three months, participated in the study. The sample was divided in two groups (kinesiotherapy and back school).The older adults were assessed before and after the therapeutic interventions. Results: both groups obtained better scoresin all the variables analyzed in the post-test in relation to the pre-test, and as a result, in the inter-group comparison, theresults did not reveal statistically significant differences (p>0.05). Conclusion: back school and conventional kinesiotherapywere effective in improving the pain, quality-of-life and agility of older adults with low back pain.